Coolest Student Papers at Finland Futures Research Centre 2017–2018 : Tulevaisuuden tutkimuskeskuksen valittuja opiskelijatöitä 2017–2018. - Tapio, Petri; Aalto, Hanna-Kaisa; Heinonen, Sirkka; Minkkinen, Matti; Puutinen, Sari; Siivonen, Katriina; Arvonen, Anne (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This eBook contains the inspired and inspiring picks from the student essays written by students and student groups in the courses organised by Finland Futures Research Centre (FFRC). This year’s selection shows that brilliant new students arrive our courses. The topics range from sustainability transitions to corporate foresight, from ethics to methodology, from data business to geoengineering. Independent, constructively critical open deliberation of how futures studies should be carried out is one of the core goals of our education and a key to further development of the courses and the whole field of futures studies.